A study on the goal setting method for increasing the holed probability in slope putting stroke on an artificial putting surface during - Park, J; Kim, J. H.; Jung, J. M. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to develop a goal setting method for increasing the probability of a holed in a side inclined putting stroke. Method: Three-dimensional video data was recorded at a frequency of 120 hz per second after synchronizing 19 infrared motion capture systems (Qualisys, Gothenburg, Sweden). Putting green used a polycarbonate plate (1.2 x 2.4 x 0.01 meter) with coefficient of friction (µ=0.062) and a real curve of the actual hole. Results: The velocity ratio between the club and the ball was 1:1.6 under various ball speed conditions in this study. The overall position of the break is 1 m to 1.4 m from the point where the ball leaves. If there is a slope, the ball follows the target line by the straightening force, and when it reaches 1 m position, the straightening force decreases by 30~50% and reaches to the deviation (break) point which is severely influenced by the slope. From here, the ball is aimed in a direction other than the target, and the size is affected by the slope. Conclusion: If there is a side slope, the ball moves away from the straight line, and the larger the slope, the closer the break point is to the starting point of the ball. Therefore, it is necessary to calculate the degree of departure according to the slope carefully, and it is preferable that the slower the speed is, the more the influence of the slope becomes. It is preferable to use the center of the hole as a reference when calculating the departure.